Introductory concepts in limb anatomy - Hartmann, Carol (Henry Stewart Talks, 2021)
Microstructure of bones, Classification of bones, Blood supply to bones, Compartmental arrangement of muscles, Functional classification of muscles, Classification and function of joints, Structure and stability of joints